A Bulk-Heterostructure Nanocomposite Electrolyte of Ce0.8Sm0.2O2-δ–SrTiO3 for Low-Temperature Solid Oxide Fuel Cells - Cai, Yixiao; Chen, Yang; Akbar, Muhammad; Jin, Bin; Tu, Zhengwen; Mushtaq, Naveed; Wang, Baoyuan; Qu, Xiangyang; Xia, Chen; Huang, Yizhong (Nano-Micro Letters, 2021)
Since colossal ionic conductivity was detected in the planar heterostructures consisting of fluorite and perovskite, heterostructures have drawn great research interest as potential electrolytes for solid oxide fuel cells (SOFCs). However, so far, the practical uses of such promising material have failed to materialize in SOFCs due to the short circuit risk caused by SrTiO3. In this study, a series of fluorite/perovskite heterostructures made of Sm-doped CeO2 and SrTiO3 (SDC–STO) are developed in a new bulk-heterostructure form and evaluated as electrolytes. The prepared cells exhibit a peak power density of 892 mW cm−2 along with open circuit voltage of 1.1 V at 550 °C for the optimal composition of 4SDC–6STO. Further electrical studies reveal a high ionic conductivity of 0.05–0.14 S cm−1 at 450–550 °C, which shows remarkable enhancement compared to that of simplex SDC. Via AC impedance analysis, it has been shown that the small grain-boundary and electrode polarization resistances play the major roles in resulting in the superior performance. Furthermore, a Schottky junction effect is proposed by considering the work functions and electronic affinities to interpret the avoidance of short circuit in the SDC–STO cell. Our findings thus indicate a new insight to design electrolytes for low-temperature SOFCs. Highlights: 1 Bulk-heterostructure electrolytes based on Ce0.8Sm0.2O2-δ and SrTiO3 are developed for solid oxide fuel cells 2 The interface characteristics are investigated to understand the fast ionic transport obtained in the heterostructure. 3 The Schottky junction effect is proposed by taking account of work functions and electronic affinities for the first time.